How Does the Heterogeneity of Internal Control Weakness Affect R&D Investment?. Issue 15 (8th December 2019) - Li, Wanfu; Han, Yuling; He, Jiangang
ABSTRACT: Internal control of nonfinancial reporting has received attention in the Committee of Sponsoring Organizations of the Treadway Commission's new Internal Control-Integrated Framework . This paper explores the effect of internal control weakness (ICW) in financial reporting and nonfinancial reporting on R&D investment. Our results show that ICWs in financial and nonfinancial reporting inhibits R&D investment, and this effect comes mainly from ICWs in nonfinancial reporting. The impact of ICW in nonfinancial reporting on R&D investment is more serious at technology-intensive companies than labor- or capital-intensive companies. The influence of heterogeneous ICW on investment in corporate innovation has time lag effect and takes at least two paths of impact: weakening of executive compensation incentives and internal cash flow oversight. These results suggest that the ICW in nonfinancial reporting play a more important role in the allocation of resources for technological innovation.